Penerapan media audio visual dalam meningkatkan hasil belajar dribble bolabasket - Ramadhan, Faizan; Yulianti, Mimi; Henjilito, Raffly (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
The purpose of this study is to improve the learning outcomes of basketball dribble techniques through the method of Audio Visual media in basketball games class IX IPS 5 SMAN 3 Mandau. This type of research is PTK, the population in the study amounted to 28 students. then the sample taken is total sampling, which is the entire population of 28 students used as samples. Based on the results of data processing in the first cycle there were 9 students who achieved the KKM value (32%), and 19 students who had not yet achieved the KKM value (68%). Classical completeness is achieved when it reaches 80%, in cycle II as many as 25 students have achieved completeness value of 89%. And as many as 3 students who have not yet reached the grade of 11%. Thus it can be concluded that there is a very significant increase in basketball dribble learning outcomes through audio-visual media in the sport of basketball class IX IPS 5 SMA N 3 Mandau Bengkalis Regency.